The church : God's pilgrim people - Niringiye, David Zac (Langham Global Library, 2014)
"David Zach Niringiye takes us on the journey of a pilgrim people, helping us appreciate what the church is at all times and in all places. This introduction provides a biblical theology that tells the story of the people and promise of God from Moses to the kingdom of God in Christ and the work of his people through the Holy Spirit." -- Back Cover